THE APPLICATION OF MORALITY, ETHICS AND CODE OF CONDUCT WITH THE THREEFOLD TRAINING TO BE THE PROFESSIONAL SCHOOL ADMINISTRATORS - Wichathikun, Pidawan; Suwannasombat, Lakprapa; Nilkote, Reongwit; Warabamrungkul, Theerangkoon; Boonloy, Waiwoot (Journal of MCU Nakhondhat, 2021)
The professional school administrators must be leaders with morals, ethics and professional ethics. Resulting in operational satisfaction resulting in efficient performance of the organization or school. The Ministry of Education therefore emphasizes on educational institution administrators to have knowledge and morals. Focus on the development and empowerment of people. With strategies for school administrators have leadership potential with sustainable management mind. And realize their roles, duties and responsibilities with pride in the professional school administrators. Including the shame of behaving badly Because the one who will be the teacher must be a good person Have faith in the profession Ready to practice the educational profession in accordance with professional standards and professional . Ethics, The application of Morality, Ethics and Code of Conduct in the Educational Administration towards A Professional school Administrators by Threefold Training. Consist of Sila (Physical behavior), Samathi (Mental training) and Panna (Enlightenment), to applied in The School Administrators Ethics comprised 4 components as follows; 1) the Ethics on personal performance, 2) the Ethics on profession, 3) the Ethics on Client, 4) the Ethics on Professional Personnel, and 5) the Ethics on Society. Can be adopt that approach, build skills of personal excellence. Have a strategic thinking and innovation And academic leadership. The apply to the norm to administration, self-governance, People governance and Work governance as a perfect of the (school) administrators that is both of ethical and be aware of changing conditions. This is an important attribute of the professional school administrators that the society needs and also the image that will make the organization to great success. Including the quality of the teachers, staff and students are of perfect quality, good and good people.